Peran Keluarga dengan Resiko Harga Diri Rendah pada Pasien Tuberkulosis: Family Role in Patients with Low Self-Esteem Risk in Tuberculosis - Nasihin, Tatan Iin; Sarwili, Indri (Journal of Nursing Education and Practice, 2022)
Background: Tuberculosis is a contagious and infectious disease that can lead to physical, mental, and social changes in patients. Tuberculosis can impact the self-concept of those affected. Objective: The purpose of this study is to determine the relationship between the role of the family and the risk of low self-esteem in tuberculosis patients at the Regional Public Hospital of Bogor City. Method: This is a correlational descriptive study using a cross-sectional approach. The research sample consists of 138 tuberculosis patients who were hospitalized in the Isolation Ward of RSUD Bogor from January to July 2017. The research instrument is a questionnaire containing a list of questions to be answered by respondents, comprising 20 questions. Data analysis was conducted using the chi-square test. Results: The research results show that suboptimal family roles have a significant relationship with a p-value of 0.000, with a result of ≤ 0.05, indicating an influence of family roles on the risk of low self-esteem. Conclusion: This study describes a relationship between the role of the family and the risk of low self-esteem in tuberculosis patients at the Regional Public Hospital of Bogor City.